Additive or Synergistic Interactions Between IL-17A or IL-17F and TNF or IL-1β Depend on the Cell Type - Noack, Mélissa; Beringer, Audrey; Miossec, Pierre (Frontiers in Immunology, 2019)
Background: IL-17A has effects on several cell types and is a therapeutic target in several inflammatory diseases. IL-17F shares 50% homology and biological activities with IL-17A. It is now of interest to target both cytokines. The objective was to compare the IL-17A and IL-17F effect on cytokine production by RA synoviocytes, and to extend to other cells. Methods: Cells (RA synoviocytes, psoriasis skin fibroblasts, endothelial cells, myoblasts and hepatocytes) were cultured in the presence or not of: IL-17A, IL-17F, TNF, IL-1β alone or their combinations, IL-17A/TNF, IL-17A/IL-1β, IL-17A/TNF/IL-1β, IL-17F/TNF, IL-17F/IL-1β and IL-17F/TNF/IL-1β. All experiments were performed in parallel to reduce variability. After 48h, supernatants were recovered and IL-6 and IL-8 levels were measured by ELISA. Results: IL-17A and IL-17F alone increased significantly IL-6 and IL-8 productions by synoviocytes, with a higher effect for IL-17A. For IL-6 production, TNF or IL-1β alone had the largest effect on myoblasts (5-fold increase), while for IL-8 production, it was on skin fibroblasts (5-fold increase). The IL-17A/TNF synergistic increase was observed on all cells for IL-6; and for IL-8, except for endothelial cells. For IL-17F/TNF, except with endothelial cells, a synergistic effect was also observed, but less powerful than with IL-17A/TNF. IL-17A/IL-1β or IL-17F/IL-1β effect was cell-type dependent, with an additive effect for synoviocytes (1.6 and 2-fold increase, respectively for IL-6, and 1.8 and 2-fold increase respectively for IL-8) and a synergistic effect for hepatocytes (3.8 and 4.2-fold increase, respectively for IL-6, and 6 and 2-fold increase respectively for IL-8). The three-cytokine combination induced an additive effect for synoviocytes and a synergistic effect for skin fibroblasts. Conclusion: IL-17A and IL-17F acted similarly by inducing pro-inflammatory cytokine secretion, with a higher response intensity with IL-17A. Their activities were potentiated by the combination with TNF and IL-1β, with an effect dependent on the cell type.